Evaluation of the introduction of a 'traffic light protocol' for dose‐volume histogram constraints of organs at risk in definitive radiotherapy at Liverpool and Macarthur Cancer Therapy Centres. Issue 3 (31st March 2020) - Kasraei, Farshad; Ochoa, Cesar; Vial, Phillip; Lee, Mark T
Abstract: Introduction: Protocols have been developed in our department with recommended dose constraints for organs at risk (OAR) for each tumour site receiving definitive radiotherapy. We have developed a colour coding system to indicate when constraints are meeting objectives (green), have minor variation from planning objectives (yellow) and have major variation from planning objectives (red). We performed a quality audit to assess adherence to the protocol and to determine the rate of acute and subacute toxicities. Methods: All definitive radiotherapy dose‐volume histogram (DVH) reports generated in the first 6 months of 2017 at Liverpool and Macarthur cancer therapy centres were collected. For each radiotherapy group, the overridden dose constraints were evaluated and categorized to red and yellow. For all patients in our data set, follow‐up documents/assessments were searched for grade 3 or higher acute or subacute radiotherapy toxicity and compared with those who had overridden dose constraints. Results: There were 210 (34%) plans accepted with at least one major variation and 161 (26%) plans with minor variation. Head and neck group had the most rate of major variations (77%). The best groups in adherence to protocol were lymphoma and breast groups. In general, grade 3 toxicity was observed in 1%, 4% and 9% of patients who were in green, yellow and red categories. Overall, we noted a correlation with grade 3 toxicities between acceptable plans (green) and ones with a minor or major variation (yellow or red) (1% vs. 7% P = 0.0001). Conclusion: In conclusion this study showed an increased risk of higher grade toxicities when DVHs were beyond our departmental constraints using a 'Traffic Light System'. With this new colour coding system, we can facilitate auditing of the dose constraints in order to improve the quality of radiotherapy plans and potentially provide benchmarking for reducing toxicities in radiotherapy treatments.